MATHEMATICAL MODELING OF HIV/AIDS TRANSMISSION AMONG INJECTING DRUG USERS WITH METHADONE THERAPY - ARVIANA HAFISHA (NIM : 10108011); Pembimbing : Dr. Nuning Nuraini
This final project will analyze models for the spread of HIV/AIDS amongst a population of injecting drug users with Methadone Therapy. Start off with a brief review about HIV/AIDS and methadone therapy itself, followed up by detailed description of mathematical modeling of HIV/AIDS transmission among injecting drug users with methadone therapy. Then perform an equilibrium and stability analysis on these models. There is a critical threshold parameter Basic Reproduction Ratio (R0) which determines the behavior of the models. Basic Reproduction Ratio (R0) is expected values of secondary infections caused by a single infected individual in an entirely susceptible population and indicate whether the endemic disease appear in entirely population or not. If R0>1, it means that the endemic disease occurs in population. Otherwise, if R0<1, it means that the endemic disease will not occurs. These result are confirmed and explored further by simulation. Based on simulation, the effective way for prevent the endemic is disenchant drug users for bleach their injection equipment after use or use a disposable injection equipment. The routine HIV/AIDS examination for addict is required for controlling the spread of HIV/AIDS